The Strategic Policy of Child Marriage Prevention on Gender-Integrated (Strengthening Best Practice Areas Toward Child Marriage-Free Zones) - Trianah Sofiani (Muwazah, 2022)
This paper analyzes strategic policies for preventing child marriage in Rembang Regency. This evaluative research uses interviews, questionnaires and literature studies for data collection. The study results show that the gender-integrated policy of child marriage prevention in the Rembang district can be seen in regulations, budgets, strengthening of child groups, institutions and cooperation. Sufficient budget and human resources, including the openness of information systems, are the strengths of the policy on child marriage prevention in this area. Programs are still partial; weakness in monitoring- evaluation; weakness in gender mainstreaming commitment; gender biased organizational culture; budget politics that often change; and the fewer activity children's forum are weaknesses in this policy. There are national and international policies; orderly population administration; gender and child disaggregated data; Information Technology; collaboration with NGOs and the private sector an opportunity that must be considered for the success of this policy. Another hand, attention must be on policy threats, namely: low education; high poverty; patriarchy; child marriage traditions; ngemblok tradition; information technology; changes in the age limit for marriage; minimal community involvement; gender insight uneven and; understanding of child rights is low. Child marriage prevention policies have an impact on target groups, non-target groups, and direct and indirect costs. Optimization of child marriage prevention policies should be carried out using scheme 1, maximizing strengths to minimize threats; scheme 2, optimizing gender equality in regional apparatus organizations and; scheme 3, monitoring-evaluation is carried out periodically and structured. These schemes must pay attention to the five "appropriate" namely the appropriate choice of policies and programs, implementation, targets, environment and process appropriate.